Key role of whole genome sequencing in resolving an international outbreak of monophasic Salmonella Typhimurium linked to chocolate products - Valeska Laisnez; Amoolya Vusirikala; Charlotte Salgaard Nielsen; Vera Cantaert; Laurence Delbrassinne; Wesley Mattheus; Bavo Verhaegen; Hugues Delamare; Nathalie Jourdan-Da Silva; Raskit Lachmann; Sandra Simon; Martin Cormican; et al. (BMC Infectious Diseases)
Abstract Background In February 2022, the United Kingdom (UK) detected a cluster of monophasic Salmonella Typhimurium based on whole genome sequencing (WGS). Subsequently, several countries reported cases belonging to this cluster. Epidemiological, microbiological and traceability investigations pointed toward a chocolate food business operator (FBO) in Belgium. We describe the magnitude of the outbreak, investigations performed and control measures taken. Methods Cases were ascertained based on internationally agreed case definitions and interviewed about food consumption prior to disease onset. Analytical epidemiological studies were conducted by the UK and Ireland. The Belgian food safety authority (FSA) coordinated microbiological and traceability investigations. Results A total of 456 cases (61% female), belonging to two genetically different WGS clusters, in 14 countries of the European Union, the UK, Switzerland, Canada and the United States were linked to the outbreak, between December 2021 and June 2022. 87% of cases were younger than 10 years. Brand A chocolate eggs, marketed for children, were reported as consumed by 168 cases (80%) with information. Analytical studies in the UK and Ireland showed a significantly higher odds of disease associated with consumption of brand A chocolate products. Retrospective investigations by the FSA revealed that routine samples (raw materials, intermediate, semi-finished and finished products as well as environmental and rinse oil samples) taken by the FBO linked to the Brand A products between December 2021 and January 2022 had tested positive for salmonella. Nine isolates were submitted to EnteroBase and matched with human isolates from both WGS clusters. The authorization for production was temporarily withdrawn on 8 April 2022 and all products of brand A were recalled worldwide, followed by a decrease in cases. Conclusions A multi-country salmonellosis outbreak linked to chocolate occurred in the months before Easter 2022. International collaboration between stakeholders from epidemiological, microbiological and food safety entities with rapid sharing of WGS results from human and nonhuman isolates were key in containing the outbreak. Implementation of routine WGS on human and nonhuman isolates will strengthen public health responses to future outbreaks. The magnitude of the outbreak underlines the importance of timely and open communication of FBOs to FSAs in case of salmonella detection.